University Training in Chilean Community Psychology Today: A Subordinate Place? [la Formación Universitaria en la Psicología Comunitaria Chilena de Hoy: ¿Un Lugar Subalterno?] - Winkler-Muller, M (Pontificia Universidad Catolica de Chile, 2016)
In order to identify and characterize the presence or absence of original values and ethical and political principles that typify the discipline in community psychology (CP) training, a qualitative research was designed considering the diversity of Chilean universities. Using structural sampling, individual interviews were conducted with 10 teachers of the discipline, 26 students participated in focus groups, and 51 CP curricula and 10 programs used in universities in the Metropolitan and Valparaíso regions were reviewed. By applying grounded theory methods and conducting a selective and inclusive analysis of all sources, an interpretive model accounting for the main results and their articulation was developed. The subordinate nature of CP in psychology training stands out, mainly due to the influence of the prevailing neoliberal model. Although ethical and political dimensions are regarded as essential, they remain at the discourse level; also, institutional and contextual factors interfere with them. The teacher-student dyad is a key facilitator of the incorporation of these dimensions in CP training. It is concluded that disciplinary training is eminently theoretical and lacks proper implementation in the communities themselves. © 2016 by Psykhe.